Evaluating the impact of investment incentives - the case of the Italian Law 488 - Raffaello Bronzini; Guido De Blasio (European Regional Science Association (ERSA), 2005)
Since the second half of the '90s, investment incentives channelled through the Law 488 have represented the main policy instrument for reducing territorial disparities in Italy. From 1996 to 2003, the total amount of funds distributed to industrial firms has accounted for 16 billion of euro, involving 27,846 financed projects, mainly in southern regions. The Law 488 allows firms willing to invest in lagged areas to receive a public subsidy that covers a fraction of the investment outlays. The incentives are assigned through competitive auctions according to pre-determined specific criteria, such as the proportion of own funds invested in the project; the number of jobs involved and the value of assistance sought as a proportion of the maximum award rate applicable to the project. This paper aims at evaluating the impact of Law 488 subsidies on firms' investment by using the econometric tools of program evaluation. We employ a unique dataset provided by the Italian Ministry of Industry, which records all the firms that have requested the grants (either subsidised or non subsidised firms), and match these data with the balance sheet information from the Company Account Data Service for the period 1994-2001. Our matched dataset allows us to evaluate whether the Law 488 made it possible investments that otherwise would not have been done. In doing so, we tackle two issues that have plagued the empirical analyses so far. First, we analyse the extent to which investments have been triggered by intertemporal substitution. In expectation of the introduction of the Law 488 firms could have postponed (anticipated) investment projects originally planned for the pre (post) Law 488 period. Second, we study the role of cross-sectional substitution. Subsidised firms could have taken some of the investment opportunities that non subsidised firm would have got in absence of the incentives.
Keywords: 330